Two‐step chromatography purification of IgGs possessing sialidase activity from human blood serum. (3rd July 2014) - Kit, Yury; Bilyy, Rostyslav; Korniy, Nataliya; Tomin, Andriy; Chop'yak, Valentyna; Tolstyak, Yaroslav; Antonyuk, Volodymyr; Stoika, Rostyslav
Abstract Sialation of cell surface is known to be tightly connected with tumorigenicity, invasiveness, metastatic potential and clearance of aged cells, while sialation of immunoglobulin G (IgG) molecules determines their anti‐inflammatory properties. Recently, we have found for the first time IgG‐antibodies possessing sialidase‐like activity (sialylic abzyme) in blood serum of multiple myeloma and systemic lupus erythematosis patients. This abzyme was detected in a pool of IgGs purified by a typical procedure including immunoglobulin's precipitation with ammonium sulfate and following chromatography on protein G–Sepharose column. Here we describe a novel matrix for affinity purification of sialylic abzyme that is based on using bovine submandibular gland mucin conjugated to Sepharose matrix (mucin–Sepharose). This matrix preferentially binds sialidase‐like IgGs from a pool of sialidase‐active fraction of proteins precipitated with 50% ammonium sulfate from blood serum of the systemic lupus erythematosis patients. That allowed us to develop a new scheme of double‐step chromatography purification of sialidase‐like IgGs from human blood serum. Copyright © 2014 John Wiley & Sons, Ltd.